The End of Socialism - Otteson, James R. (Cambridge : Cambridge University Press, 2014)
Is socialism morally superior to other systems of political economy, even if it faces practical difficulties? In The End of Socialism, James R. Otteson explores socialism as a system of political economy - that is, from the perspectives of both moral philosophy and economic theory. He examines the exact nature of the practical difficulties socialism faces, which turn out to be greater than one might initially suppose, and then asks whether the moral ideals it champions - equality, fairness, and community - are important enough to warrant attempts to overcome these difficulties nonetheless, especially in light of the alleged moral failings of capitalism. The result is an examination of the'end of socialism', both in the sense of the moral goals it proposes and in the results of its unfolding logic.
Machine generated contents note: 1. What socialism and capitalism are; Part I. Socialism's Problems in Practice: 2. Knowledge and planning; 3. Knowledge: value, equality, and experts; 4. Knowledge and community; 5. The day-two problem; Part II. Socialism's Problems in Principle: 6. Economics and morality; 7. Respect and individuality; 8. Socialism's great mistake; 9. Prosperity; 10. Equality and freedom; 11. Fairness; Conclusion. Grapes sweet and sour.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Socialism